If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -30y = -27 Solving 3x + -30y = -27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30y' to each side of the equation. 3x + -30y + 30y = -27 + 30y Combine like terms: -30y + 30y = 0 3x + 0 = -27 + 30y 3x = -27 + 30y Divide each side by '3'. x = -9 + 10y Simplifying x = -9 + 10y
| -1/2v+4+2=-7/v+2 | | 3(x+15)=2(2x+10) | | 6/v+5-2/v+5=4 | | 0.8y=6 | | 16(y-9)+2y=8y-3(20) | | 5/7x1/4x+10=9/14 | | 4n-1=30 | | 4(x+6)=44 | | 7*(4(1/3))+2 | | X/-5=-11.3 | | 4(z-3)+5z-1= | | 10/5/6*6/12/6 | | 6-(4x-5)=7-5x | | 5(-1)+4=7(-1)+6 | | G+1/5=4/5 | | 2/3u-7/5u=1 | | 0=-8t^2+15t+3 | | -1/w-2=4 | | n/2+n+35=107 | | (35+n/2)+n=107 | | 6x-24+2x+10=3x+3+4 | | -8=-2/x | | 2x+6/4x-12 | | x-14=-10+21/x | | -4/7y-2+8/7y | | 4-2x=2x^2+8x-6 | | 5/9+9/-5 | | 8X-72=-8x-40 | | 35+n/2+n=107 | | 5(t-9)-6(2t+1)=-8(t+4)-2 | | 2n+5+3n= | | 1/3-4/7 |